Clinicopathological Analysis of CNS Involvement in Multiple Myeloma - Togano, Tomiteru; MINE, Sohtaro; Miwa, Akiyoshi; Hagiwara, Shotaro (Blood, 2015)
Background Extramedullary disease (EMD) is often observed in end stage of multiple myeloma (MM).However, central nervous system (CNS) involvement is very rare. Thus, little is known about CNS involvement of MM. We conducted clinicopathological analysis. Methods We reviewed medical records and pathological specimens of multiple myeloma cases between 1979 and 2015 at the National Center for Global Health and Medicine in Tokyo, Japan. Patient information and duration of illness, clinical finding including type of monoclonal protein, Durie & Salmon's (DS) staging, treatment and pathological findings were collected. CNS involvement was diagnosed pathologically. Results We found 15 cases of CNS involvement multiple myeloma. In 15 cases, 66.6 % was male. Mean age and the duration of illness were 56 years old and 35.7 months, respectively. DS stage was 3A (46 %), 2A (20 %), 2A (20 %), 1A (13 %). Monoclonal protein was IgG (46 %), IgA (33 %), BJP (0.6 %) and non-secretary (13 %). Lambda chain was 62 %. Manifestation at diagnosis CNS involvement was disturbance of consciousness (40 %), visual disturbance (20 %), dysphagia (13%), paresthesia of extremities (20 %), vomiting or nausea (13 %). Other organ involvement was spleen (60 %), pancreas (53 %), liver (53 %), adrenal gland (46 %), testis (31 %) and plasma cell leukemia (40 %). In two cases, peripheral nerve involvement was found. Seven of 15 patients were previously treated with novel agents such as bortezomib, thalidomide, and lenalidomide. Recent 5 years, the frequency of CNS involvement increased more than threefold (1.0 case/year), compared to 1979-2010 (0.3 case/year). In all cases, myeloma cells infiltrated dura mater or subarachnoid cavity. Infiltration in parenchyma of brain was seen in only 2cases. Myeloma cells were seen at loose section of connective tissue around vascular in most cases. Interestingly, myeloma cells were often infiltrated at peripheral nerve, spinal cord cavity and central canal without spinal cord. Conclusions In the era of novel agents, the incidence of CNS involvement in patients with multiple myeloma has increased. We found myeloma cells were often infiltrated at peripheral nerve, spinal cord cavity and central canal without spinal cord. Our study revealed that exposure to novel agents, lambda type MM, multi-organ involvement and plasma cell leukemia were associated with CNS involvement. Hagiwara:Celgene Corporation: Membership on an entity's Board of Directors or advisory committees.